A potent Lassa virus antiviral targets an arenavirus virulence determinant - Madu, Ikenna G. (PLoS Pathog, 2018)
Arenaviruses are a significant cause of hemorrhagic fever, an often-fatal disease for which there is no approved antiviral therapy. Lassa fever in particular generates high morbidity and mortality in West Africa, where the disease is endemic, and a recent outbreak in Nigeria was larger and more geographically diverse than usual. We are developing LHF-535, a small-molecule viral entry inhibitor that targets the arenavirus envelope glycoprotein, as a therapeutic candidate for Lassa fever and other hemorrhagic fevers of arenavirus origin. Using a lentiviral pseudotype infectivity assay, we determined that LHF-535 had sub-nanomolar potency against the viral envelope glycoproteins from all Lassa virus lineages, with the exception of the glycoprotein from the LP strain from lineage I, which was 100-fold less sensitive than that of other strains. This reduced sensitivity was mediated by a unique amino acid substitution, V434I, in the transmembrane domain of the envelope glycoprotein GP2 subunit. This position corresponds to the attenuation determinant of Candid#1, a live-attenuated Junín virus vaccine strain used to prevent Argentine hemorrhagic fever. Using a virus-yield reduction assay, we determined that LHF-535 potently inhibited Junín virus, but not Candid#1, and the Candid#1 attenuation determinant, F427I, regulated this difference in sensitivity. We also demonstrated that a daily oral dose of LHF-535 at 10 mg/kg protected mice from a lethal dose of Tacaribe virus. Serial passage of Tacaribe virus in LHF-535-treated Vero cells yielded viruses that were resistant to LHF-535, and the majority of drug-resistant viruses exhibited attenuated pathogenesis. These findings provide a framework for the clinical development of LHF-535 as a broad-spectrum inhibitor of arenavirus entry and provide an important context for monitoring the emergence of drug-resistant viruses.